Architectonics of the root system of Japanese persimmon depending on rootstock and relief - M. D. Omarov; Z. M. Omarova (Новые технологии)
The article presents the long-term results of excavations of the root system of 10-year-old Japanese persimmon plants (‘Hiakume’ variety), grafted on two rootstocks (Oriental persimmon and common persimmon). It has been established that biological characteristics of rootstocks, topography, and tillage in the aisles affect significantly the total mass of the roots, as well as its distribution in the soil layers. Plants grafted on Oriental persimmon have a more developed and deeply penetrating root system. It is noted that on the slopes the development of the root system is uneven. The bulk of the roots is directed up the slope (72%), so a larger amount of mineral fertilizers must be applied to the upper terrace. On a flat site, the development of the root system occurs evenly around the crown of the plant, the roots are more powerful than those growing on the slope. Differences in remoteness from the stem have not been noted; in both cases, the roots have been placed at a distance of up to 250 cm in the aisle. As a result of the research, a direct relationship between the growth of the aerial part and the development of the root system has been determined, the stronger the aerial, the more powerful the root system.